Control biológico del sobreentrenamiento en un mesociclo precompetitivo en triatletas de élite: un estudio piloto. - Diaz Molina, V.; Diaz Martinez, E.; Belen Peinado, A.; Benito, P. J.; Calderon, F. J.; Sampedro, J. (Archivos de medicina del deporte, 2010)
The aim of this study was to control the evolution of biochemical parameters commonly associated with overtraining in five weeks before a major competition in elite triathletes. During five weeks, training was controlled in five elite male elite triathletes (VO2max 77,6±5,1 mL•min•kg-1). In this period, microcyles structure was fixed with one day of high load followed by another of recovery. The days after the loading and recovery blood samples were obtained to determine the concentration of urea (U), creatine kinase (CK), total testosterone (T) and total cortisol (C). Training volume was obtained from distances covered in swimming, cycling and running. Total volume training changed from a maximum of 78,1 km duing microcycle 3 and 40,8 km during microcycle 4. Both, U and CK experienced a significant increase (compared with reference values at the start of the season) during loading in four of the five weeks of study. Moreover, following the recovery, these parameters did not returned to the baseline levels in two weeks for the CK and three weeks for the U. However, triathletes did not report any overtraining symptom as lack of sleep. Furthermore, the relación T/C did not fall more than 30% of the analytical reference. Thus, we concluded that the elite triathletes do not experience symptoms of overtraining during the weeks before a competition, at least when it is assessed by biochemical parameters.